Electronic and Optical Properties of 2D Materials Constructed from Light Atoms. Issue 46 (7th August 2018) - Weng, Qunhong; Li, Guodong; Feng, Xinliang; Nielsch, Kornelius; Golberg, Dmitri; Schmidt, Oliver G.
Abstract: Boron, carbon, nitrogen, and oxygen atoms can form various building blocks for further construction of structurally well‐defined 2D materials (2DMs). Both in theory and experiment, it has been documented that the electronic structures and optical properties of 2DMs are well tunable through a rational design of the material structure. Here, the recent progress on 2DMs that are composed of B, C, N, and O elements is introduced, including borophene, graphene, h‐BN, g‐C3 N4, organic 2D polymers (2DPs), etc. Attention is put on the band structure/bandgap engineering for these materials through a variety of methodologies, such as chemical modifications, layer number and atomic structure control, change of conjugation degree, etc. The optical properties, such as photoluminescence, thermoluminescence, single photon emission, as well as the associated applications in bioimaging and sensing, are discussed in detail and highlighted. Abstract : 2D materials constructed from boron, carbon, nitrogen, and oxygen atoms show a rich structural diversity. This makes possible engineering of their electronic and optical properties through a refined structural control.